2019
DOI: 10.1302/0301-620x.101b5.bjj-2018-1478.r1
|View full text |Cite
|
Sign up to set email alerts
|

Is end-organ surveillance necessary in patients with well-functioning metal-on-metal hip resurfacings?

Abstract: Aims Cardiac magnetic resonance (CMR) was used to assess whether cardiac function or tissue composition was affected in patients with well-functioning metal-on-metal hip resurfacing arthroplasties (MoMHRA) when compared with a group of controls, and to assess if metal ion levels correlated with any of the functional or structural parameters studied. Patients and Methods In all, 30 participants with no significant cardiac history were enrolled: 20 patients with well-functioning MoMHRA at mean follow-up of 8.3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A small increase in heart complications in metal bearing surfaces compared to non-metal surfaces was identified after controlling for confounding factors and this was most pronounced in MoM versus CoC in patients over 75 years of age. 68 These studies represent a range of different experimental designs including cross-sectional observational studies 65 , 66 and population-based cohort studies, 67 , 68 and they find broadly similar results.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A small increase in heart complications in metal bearing surfaces compared to non-metal surfaces was identified after controlling for confounding factors and this was most pronounced in MoM versus CoC in patients over 75 years of age. 68 These studies represent a range of different experimental designs including cross-sectional observational studies 65 , 66 and population-based cohort studies, 67 , 68 and they find broadly similar results.…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that adverse cardiac processes may be at work in asymptomatic MoM patients, even when they have normal or minimally elevated blood cobalt levels. 66 Population-wide studies have demonstrated cardiac complications in MoM patients without studying individual blood cobalt levels. A retrospective cohort study of the Australian Government Department of Veterans’ Affairs demonstrated that men with an ASR XL THA had a statistically significant higher rate of hospitalization for heart failure than men with a MoP THA.…”
Section: Discussionmentioning
confidence: 99%
“…Berber et al [53] evaluated 90 patients with either ceramic on ceramic, MoM hips with low ion levels, and MoM hips with high ion levels (>7 µg L -1 ). In this study, there was no difference in cardiac MRI results.…”
Section: Cardiotoxicitymentioning
confidence: 99%